"Er hat geschmack, und über das die größte Compositionswissenschaft": Geschmack, Fertigkeit und Kreativität in Mozarts "Haydn"-Streichquartetten - Irving, John (Die Musikforschung, 2004)
Leopold Mozart's letter to his daughter of 16 February 1785, describing a performance of Wolfgang Amadeus Mozart's latest string quartets in the presence of Joseph Haydn claims that Haydn considered Mozart to have taste, and also a profound knowledge of composition. Contrasting interpretations of this statement are considered, including the relationship between taste and compositional technique, involving discussion of some sketches for Mozart's quartets and investigation of Haydn's statement against the background of 18th-century aesthetics.